2010
DOI: 10.5114/aoms.2010.13510
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of TGF-b1 genotypes in Egyptian smokers; association with FEV1 in COPD patients

Abstract: IntroductionTGF-β1 is a cytokine with many different effects on cell proliferation, differentiation and inflammation and can protect against the development of COPD. This work aims to study the association between COPD and the TGF-β1 gene genotypes.Material and methodsThe study included 70 males: 25 smokers with COPD, 25 resistant smokers, and 20 normal non-smokers as the control. They were subjected to spirometry pre- and post-bronchodilator (FEV1, FEV1/FVC), estimation of serum level of TGF-β1 gene by PCR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…These findings supported the hypothesis that the two treatments, especially BY granule, benefited to patients with COPD in clinical practice. Interestingly, TGF-β1 could delay the development of COPD, and help repair damage to the lungs of individuals who are at risk of developing COPD, preserving the decline of FEV 1 [20] , [21] . Recent researches provided the levels of TGF-β1 were different at four stages of COPD with highest in stage IV, and inversely correlated with FEV 1 (% predicted) and FVC (% predicted) [22] , [23] .…”
Section: Discussionmentioning
confidence: 99%
“…These findings supported the hypothesis that the two treatments, especially BY granule, benefited to patients with COPD in clinical practice. Interestingly, TGF-β1 could delay the development of COPD, and help repair damage to the lungs of individuals who are at risk of developing COPD, preserving the decline of FEV 1 [20] , [21] . Recent researches provided the levels of TGF-β1 were different at four stages of COPD with highest in stage IV, and inversely correlated with FEV 1 (% predicted) and FVC (% predicted) [22] , [23] .…”
Section: Discussionmentioning
confidence: 99%
“…In a case control study, the distribution of TGF-β1 genotypes in an Egyptian population was demonstrated; the absence of the Pro-Pro alleles in all cases of the study denoted a high predisposition to COPD in Egyptian smokers. Moreover, the Pro allele of the TGF-β1 gene was expressed more commonly in resistant smokers than in smokers who developed COPD, demonstrating a protective role against COPD and an important effect in preserving further decline in forced expiratory volume in the 1 s (FEV 1 ) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%